2009
DOI: 10.1080/02841850902889846
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 3-Tesla magnetic resonance imaging for the staging of prostate cancer in comparison to the partin tables

Abstract: 3T MRI showed a high accuracy for the staging of clinically localized prostate cancer, and it was significantly more accurate in predicting the final pathological stage than the Partin tables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…The detection of cancers having extracapsular extension (ECE) might be improved by using high power field MRI. Three tesla MRI (3T-MRI) is reported to have higher sensitivity and specificity (66.7% and 100%) for detection of ECE in PCa than 1.5T-MRI [10].…”
Section: Discussionmentioning
confidence: 99%
“…The detection of cancers having extracapsular extension (ECE) might be improved by using high power field MRI. Three tesla MRI (3T-MRI) is reported to have higher sensitivity and specificity (66.7% and 100%) for detection of ECE in PCa than 1.5T-MRI [10].…”
Section: Discussionmentioning
confidence: 99%
“…As with 1.5T MRIs, ERCs cause significant changes in the prostate dimensions and a significant volume decrease, making image registration with the radiation treatment planning CT challenging [4]. Some investigators have suggested the resolution provided by 3T MRI without an ERC is as good as the 1.5T MRIs with an ERC [5][6][7][8]. Although performing 3T MRI without an ERC would have a number of advantages, including less patient discomfort, lower costs, and better correlation with RT planning, it is not widely available.…”
Section: Mri Treatment Planningmentioning
confidence: 99%
“…Owing to the large variety of study conditions, in particular with respect to patient groups, readers and methodology, it is generally difficult to evaluate the results independently. For 3 T studies without an endorectal coil, however, it can be observed that either the sensitivity [8, 20,23] or specificity was found to be below 80 % [6] while both values were higher than 80 % [8,18] in two studies with an endorectal coil, at least for experienced prostate MRI readers (3 years, 250 cases). The good local staging accuracy of 3 T MRI with an endorectal coil, with sensitivities and specificities for ECE and SVI detection largely above 80 %, is confirmed in this study.…”
Section: Urogenital Tract 799mentioning
confidence: 99%